Genome-wide identification and expression analysis of 3-ketoacyl-CoA synthase gene family in rice (Oryza sativa L.) under cadmium stress - Yang, Lingwei; Fang, Junchao; Wang, Jingxin; Hui, Suozhen; Zhou, Liang; Xu, Bo; Chen, Yujuan; Zhang, Yuanyuan; Lai, Changkai; Jiao, Guiai; Sheng, Zhonghua; Wei, Xiangjin; et al. (Frontiers in Plant Science, 2023)
3-Ketoacyl-CoA synthase (KCS) is the key rate-limiting enzyme for the synthesis of very long-chain fatty acids (VLCFA) in plants, which determines the carbon chain length of VLCFA. However, a comprehensive study of KCSs in Oryza sativa has not been reported yet. In this study, we identified 22 OsKCS genes in rice, which are unevenly distributed on 9 chromosomes. The OsKCS gene family is divided into six subclasses. Many cis-acting elements related to plant growth, light, hormone and stress response were enriched in the promoters of OsKCS genes. Gene duplication played a crucial role in the expansion of the OsKCS gene family and underwent a strong purifying selection. qRT-PCR results revealed that most KCS genes are constitutively expressed. We also revealed that KCS genes responded differently to exogenous cadmium stress in japonica and indica background, and the KCS genes with higher expression in leaves and seeds may have functions under cadmium stress. This study provides a basis for further understanding the functions of KCS genes and the biosynthesis of VLCFA in rice.